Several Lipophilic Components of Five Elite Genotypes of Romanian Seabuckthorn (Hippophae rhamnoides subs. carpatica) - Liviu Adrian VESCAN (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2010)
Seabuckthorn is a spinescent, deciduous and dioecious berry-producing shrub, with a high economical and ecological potential. It is frequently used as a pioneer species in anthropic and eroded soils due to its low pedoclimatic demands, strong rooting system and ability to fix atmospheric nitrogen. Seabuckthorn berries, leaves and bark have a high content of nutritive and active substances which promote this species for use in both food and medical industries. One of the most requested therapeutical products on the market is the seabuckthorn oil, extracted from both pulp and seeds. Two important parameters in analyzing seabuckthorn oil quality are fatty acids and tocopherols. In Transylvania region most of seabuckthorn orchards are established with local, low productive and less uniform planting material, randomly collected from wild flora. In order to assess the opportunity of introducing new seabuckthorn varieties in Transylvania, a selection process was initiated. In this context, five elites were selected from wild populations in the Danube Delta, using biometrical criteria. They were later compared to a representative individual from a local population and to a number of homologated cultivars, with respect to morphology and some lipophilic components (oil content, fatty acids and tocopherols). For both pulp and seeds, total lipids were extracted using a modified Folch method. Fatty acids were analyzed by gas chromatography using flame ionization detection. Tocopherols were analysed using a Shimadzu VP Series liquid chromatograph with a fluorescence detector FR-10 AXL.